A Fortieth-Anniversary Reappraisal of `Chalcedon: End or Beginning?’ - Krieg, Robert A. (Philosophy & theology, 1995)
This essay shows why Karl Rahner’s “Chalcedon: End or Beginning?,” also titled “Current Problems in Christology” (1954), stands as a breakthrough in contemporary Catholic Christology. After describing the Neo-Thomism and Neo-Scholasticism of the early twentieth century, it examines one instance of this body of thought: Reginald Garrigou-Lagrange’s “Christ the Savior” (1946). Then, the essay reviews the argument of “Chalcedon: End or Beginning?” Finally, it contrasts Garrigou-Lagrange’s literal Thomism and Rahner’s transcendental Thomism.